How do patients and professionals differentiate between intra‐articular joint bleeds and acute flare‐ups of arthropathy in patients with haemophilia?. (3rd December 2015) - Timmer, M. A.; Pisters, M. F.; de Kleijn, P.; Veenhof, C.; Laros‐van Gorkom, B. A. P.; Kruip, M. J. H. A.; de Bie, R. A.; Schutgens, R. E. G.
Abstract : Introduction: The overlap in symptoms between joint bleeds and flare‐ups of haemophilia arthropathy (HA) creates difficulties in differentiating between the two conditions. Diagnosis of haemarthrosis is currently empirically made based upon clinical presentations. However, no standard diagnostic criteria are available. To offer appropriate treatment, rapid and accurate diagnosis is essential. Additionally, adequate differentiation can decrease health costs significantly. Aim: The aim of this study was to identify signs and symptoms to differentiate between an intra‐articular joint bleed and an acute flare‐up of HA in patients with haemophilia and make an initial proposal of items to include in a diagnostic criteria set. Methods: Six focus group interviews with a total of 13 patients and 15 professionals were carried out. The focus groups were structured following the Nominal Group Technique (NGT). Results: The most important signs and symptoms used to differentiate between joint bleeds and HA were (i) course of the symptoms, (ii) cause of the complaints, (iii) joint history, (iv) type of pain and (v) degree of impairments in range of motion. Conclusion: This qualitative study provides insight into signs and symptoms that are currently used to differentiate between joint bleeds and flare‐ups of HA. Results of this study can be used to develop a valid and standardized clinical diagnostic criteria set to differentiate between these two conditions. Further research is necessary to validate the signs and symptoms found in this study.